Single-cell transcriptomics unveils leukocyte heterogeneity in the gills of Larimichthys crocea in response to parasitic infection - Li, Qiuhua; Wang, Meiyan; Li, Chenhao; Tran, Ngoc Tuan; Ao, Jingqun; Li, Shengkang; Chen, Xinhua (Frontiers in Immunology, 2025)
BackgroundFish gills serve as critical immune interfaces against aquatic pathogens, yet their leukocyte heterogeneity in response to parasitic infections remains poorly understood.MethodsSingle-cell RNA sequencing was employed to elucidate leukocyte responses in the gills of Larimichthys crocea during Cryptocaryon irritans infection.ResultsA total of 13,070 leukocytes from the gills under steady-state and infected conditions were profiled and classified into eight principal lineages: T cells (> 70% of total immune cells), ILC2-like cells, NK-like cells, neutrophils, cpa5+ granulocytes, B cells, macrophages, and dendritic cells. Following infection, T cell subsets exhibited distinct responses: Regulatory T cells expanded and demonstrated immunoregulatory capacity; CD8+ T cells exhibited cytotoxic responses; CD4-CD8- T cells displayed Th17-like functions; and γδ T cells showed Th2-like activity. ILC2-like cells significantly increased in abundance and upregulated type 2 cytokine expression, whereas cytotoxic NK-like cells enhanced chemokine signaling and cytotoxicity. Neutrophils increased in number and oxidative activity, while cpa5+ granulocytes highlighted immunomodulatory functions. Macrophages, dendritic cells, and B cells exhibited compartmentalized activation states, upregulating gene modules associated with pathogen recognition, antigen processing/presentation, chemotactic activity, and antibody defenses.ConclusionsThese findings describe a multi-layered immune cell defense strategy in the gills of teleosts against parasitic infection, showing conserved and fish-specific adaptations. Understanding gill immunity provides viable targets for enhancing parasite resistance in aquaculture, such as modulating ILC2/Treg pathways to prevent infections.